The Transformation of Social Values in the Digital Era: A Study on Changing Family Relations Among the Middle Class - Nurhaliza, Nurhaliza; Savandha, Septien Dwi (Journal Of Social Science (JoSS), 2025)
The digital era has brought significant changes to various aspects of social life, including the structure and dynamics of family relationships. Among the middle class, the high penetration of digital technology has led to a transformation of social values that have traditionally underpinned family relations, such as togetherness, parental authority, and face-to-face communication. This article aims to examine how social values within middle-class families have shifted as a result of digitalization, and how family members renegotiate their roles and relationships in this context. This research adopts a qualitative approach using a case study method involving five urban middle-class families in Indonesia. Data collection techniques include in-depth interviews, participant observation, and analysis of digital documents (social media and family digital communication). The findings reveal that digital technology mediates relationships among family members in ambivalent ways: on one hand, it strengthens connectivity; on the other hand, it triggers fragmentation of interactions and redefinitions of values such as intimacy, discipline, and authority. Traditional values are being transformed into new, more flexible forms, which are also vulnerable to conflict and generational gaps. This study highlights the importance of critical awareness within families in managing technology use to maintain social cohesion within the household.